Improving Students' Performance on the Use of the Microscope through Demonstration Method - Awuah, Frank; Siemoh, Robert Kwadwo (Jurnal Pendidikan Matematika dan Sains, 2024)
This study became necessary following the difficulty in teaching the microbial aspect of biology with a single microscope in the Abetifi Presbyterian College of Education. The main objective of this research is to investigate the effectiveness of the demonstration approach in improving students' performance in using the only microscope at Abetifi Presbyterian College of Education. The population of this study which employed action research, consisted of all seventy (70) teacher candidates in this class. The study employed simple random sampling method to select sixty respondents to represent this population. The research instruments in this study were test and questionnaire. According to the study, students learn how to use a microscope more effectively when they are taught through a demonstration method as opposed to a lecture method even in a situation of woefully inadequate teaching learning materials (TLMs). Therefore, the study recommends in-service training for science teachers on demonstration methods, particularly in resource-limited settings.